CONSTITUTIONAL CONTROL OF EMERGENCY POWERS IN INDONESIA'S PRESIDENTIAL SYSTEM: KONTROL KONSTITUSIONAL ATAS WEWENANG DARURAT DALAM SISTEM PRESIDEN INDONESIA - Ahmad Ainun Najib (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
The constitutional regulation of emergency powers presents a significant challenge for contemporary constitutional democracies, particularly within presidential systems where executive authority often expands during crises. In Indonesia, this issue is encapsulated in Article 12 of the 1945 Constitution, which grants the President the authority to declare a state of emergency without clearly delineating substantive thresholds, temporal limits, or institutional mechanisms of control. The ongoing reliance on Law No. 23 Prp of 1959 further entrenches a security-oriented framework that increasingly diverges from Indonesia’s post-amendment constitutional commitment to the rule of law and human rights protection. This article explores constitutional controls over emergency powers in Indonesia through a doctrinal and comparative constitutional analysis. It assesses the normative coherence and institutional adequacy of Indonesia’s emergency powers framework by situating it in a comparative perspective with South Korea and Brazil, two presidential systems that have developed more structured constitutional mechanisms for regulating emergencies. The comparison emphasizes differentiated emergency regimes, legislative involvement, temporal limitations, and judicial oversight as key tools for constraining executive discretion during crises. The article concludes that Indonesia’s emergency powers framework remains normatively under-specified and institutionally fragile, resulting in fragmented emergency governance and weak constitutional accountability. Drawing on comparative insights, the article identifies reform implications aimed at strengthening constitutional controls, particularly through clearer emergency standards, enhanced legislative and judicial oversight, and the reconceptualization of emergency powers as a constitutionally regulated exception rather than an open-ended executive prerogative.